Religiosity and Anti-Corruption Perceptions of Students - Adi Heryadi; Egi Prawita; Alvira Laylhi Shoma Hikma Wirandha (Bisma The Journal of Counseling, 2022)
Students are the future cadres of the nation, but not infrequently students behave dishonestly in academic life on campus. Continuous efforts are needed to build students' anti-corruption perceptions so that in the future they will not behave in corruption. religiosity is religiosity that includes various dimensions that not only occur when a person performs ritual behavior (worship), but also performs other activities. This study aims to see the relationship between Religiosity and Anti-Corruption Perceptions of Students, this correlational study uses a religiosity scale and an anti-corruption perception scale as a data collection tool. Respondents of this study were students of the Faculty of Economics and Social Unjaya who were selected by purposive sampling technique and 132 respondents were collected. The results showed that there was a positive relationship between religiosity and anti-corruption perception, the higher the student's religiosity, the higher the anti-corruption perception. The religiosity variable contributed 43% to the anti-corruption perception variable.